Reef Fish Beware! Aggressive Mimicry in a Pycnodontid? - Kölbl-Ebert, Martina; Ebert, Martin; Bellwood, David R.; Schulbert, Christian (Abstracts of the 90th Annual Meeting of the Paläontologische Gesellschaft, 2019)
Pycnodontiformes are an extinct order of Actinopterygian fishes, present from the Late Triassic (Norian) to the Eocene. Their mostly deep, laterally compressed bodies and comparatively large fins indicate that these fishes were mostly highly manoeuvrable reef fish. With their characteristic durophagous dentition, columnar to incisiform anterior teeth (on premaxilla and dentary) and the posterior crushing teeth of the prearticular and vomer, the whole group was highly specialized as predators on hard-shelled organisms. In 2016, however, a new pycnodontid was found in the quarry of Ettling (Markt Pförring, Bavaria; Late Jurassic) by the excavation team of the Jura-Museum Eichstätt. The most striking feature of this new pycnodontid, Piranhamesodon pinnatomus Kölbl-Ebert et al., 2018 (JME-ETT4103), is its unusual dentition: It has long, pointed teeth at the front (on premaxilla and dentary), dagger-shaped teeth with a sharp, posterior cutting edge along the exterior-most tooth row of the vomer, and triangular teeth with serrations on their anterior margin along the exterior-most tooth row of the prearticulars. As revealed by CT-scanning, the inner teeth of prearticular and vomer are limpet-shaped cones on a columnar tooth base. The “fangs” along the exterior-most tooth row of the prearticulars and vomer of Piranhamesodon pinnatomus interact like scissors; a comparison of their functional morphology with other actinopterygians stress the exceptional high bite-force (a legacy of their pycnodont ancestry), which is comparable to modern piranhas, suggesting a completely unusual mode of predation compared to all other known pycnodontids. We propose this species to have exploited aggressive mimicry: Seemingly harmless and inconspicuous through the typical pycnodontid shape and possibly aided by corresponding colouring, it may have approached and then attacked unsuspecting other fish in the reef, biting and tearing a mouthful of flesh or fin from their unwary prey. Alternatively, it may also have acted at least occasionally as scavenger.<br
Keywords: Pycnodontiformes; Piranhamesodon; Late Jurassic; Ettling